The Influence of Communication and Work Environment on the Performance of Junior Highschool State 13 Bogor Teachers - Sartika, Rawit; Sutrariadi, Panji (International Journal of Social Service and Research, 2023)
This study aims to explain the effect of communication on teacher performance, work environment on teacher performance, and communication and work environment on teacher performance at Junior Highschool State 13 Bogor. Quantitative descriptive methods were used in this study. The population is teachers of Junior Highschool State 13 Bofor with a sample of 100 teachers taken using a simple random sampling technique. Research instruments using questionnaires. Data analysis uses multiple linear regression tests by performing t tests, F tests, and coefficient of determination (R Square) analysis. The results showed that communication has an influence on teacher performance, the work environment has an influence on teacher performance, and communication and work environment have an influence on teacher performance at Junior Highschool State 13 BOGOR.